Pacing of Red Sea Deep Water Renewal During the Last Centuries. Issue 8 (23rd April 2019) - Felis, Thomas; Mudelsee, Manfred
Abstract: The Red Sea is a deep marine basin often considered as small‐scale version of the global ocean. Hydrographic observations and ocean‐atmosphere modeling indicate Red Sea deep water was episodically renewed by wintertime open‐ocean deep convections during 1982–2001, suggesting a renewal time on the order of a decade. However, the long‐term pacing of Red Sea deep water renewals is largely uncertain. We use an annually resolved coral oxygen isotope record of winter surface water conditions to show that the late twentieth century deep water renewals were probably unusual in the context of the preceding 100 years. More frequent major events are detected during the late Little Ice Age, particularly during the early nineteenth century characterized by large tropical volcanic eruptions. We conclude that Red Sea deep water renewal time is on the order of a decade up to a century, depending on the mean climatic conditions and large‐scale interannual climate forcing. Plain Language Summary: The Red Sea is a deep marine basin often considered as small‐scale version of the global ocean. Hydrographic observations and ocean‐atmosphere modeling indicate Red Sea deep water was episodically renewed by wintertime open‐ocean deep convections in the northern Red Sea during 1982–2001, suggesting a deep water renewal time on the order of a decade. However, the long‐term pacing of Red Sea deep water renewals is largely uncertain, due to lack of hydrographic observations. By using an annually resolved coral oxygen isotope record of winter surface water conditions in the northern Red Sea we show that the late twentieth century deep water renewals were probably unusual in the context of the preceding 100 years. Our results suggest an absence of major deep water formation events until the 1883 Krakatau volcanic eruption. More frequent major events are detected during the late Little Ice Age, particularly during the early nineteenth century characterized by large tropical volcanic eruptions. From our long‐term perspective we conclude that Red Sea deep water renewal time is on the order of a decade up to a century, depending on the mean climatic conditions and large‐scale interannual climate forcing, which should be considered in management strategies of its unique ecosystems. Key Points: Observed frequent late twentieth century Red Sea deep water renewals were probably unusual in the context of the preceding 100 years Coral proxy record suggests absence of major deep water formation events until the 1883 Krakatau volcanic eruption More frequent major Red Sea deep water formation events are detected during the early nineteenth century and late Little Ice Age